Understanding plant phytochrome 3D structure and signalling mechanisms - Guan, Kaoling; Justus Liebig University Giessen (My University, 2022)
The main aim of this study was to expand our understanding of plant phytochrome action by illuminating the mysteries behind Pr-Pfr photoconversion, Pfr nuclear translocation, and phytochrome-PIF interaction via combinations of structural, biochemical, biophysical and in vivo cell biological techniques. To this end, various constructs of Glycine max (soybean) phyA and phyB were produced, purified, characterised and subjected to crystallisation trials. After great effort in the crystallisation screening, condition optimisation, X-ray diffraction trials, data processing, model building and refinement, two structures of plant phytochrome in the Pr state were determined at high resolution, namely for a PGP (nPAS-GAF-PHY) construct of phyB and a PG (nPAS-GAF) construct of phyA from Glycine max. The latter represents the first crystal structure of A-type plant phytochrome, and surprisingly showed R/FR photochromicity in the absence of the PHY domain. Together with extensive spectroscopic data, this work provides new insight into plant phytochrome structure and function. To determine plant phytochrome Pfr structures, various Pfr-stabilised and the Pfr-mimic mutants were studied similarly. Two of them, R549A and Y242H mutants of GmphyA(PGP) crystallised successfully but have yet to yield useful diffraction data. Our studies provide valuable hints for further conditions optimisations of these and novel Pfr crystallisation trials of other constructs. In addition, GmphyA(PG) crystallised under continuous or pulsed orange light with crystal packing pattern and conformation of the N-terminus of the nPAS domain quite distinct from those of the Pr crystals. The photoconverted GmphyA(PG) crystals diffract to 2 Å, providing suitable materials for further X-ray free electron laser (XFEL) studies. Nuclear translocation of phyA depends on the function of FHY1, a carrier protein bearing both nuclear localisation and nuclear export signals. Remarkably however, a KRKR motif representing a putative Class I NLS, was identified in the 380s loop of the phyA subfamily. We showed that KRKR promotes nuclear accumulation of YFP in onion epidermal cells, while a single mutation of the KRKR motif abolished this activity. Earlier work showed phyA:GFP as cytoplasmic foci in mutants lacking FHY1 function; here we found that some onion epidermal cells transfected with PHYA:GFP bearing the KRKR→AAAA mutation showed similar foci. We are eager to understand how phytochromes interact with and thereby regulate the activity of the PIF family of transcription factors at the structural level. In preparation, the interaction between GmphyB and Arabidopsis PIF6 was investigated using size exclusion chromatography. We detected Pfr-dependent interaction between the NPGP (NTE-nPAS-GAF-PHY) construct of GmphyB and PIF6 as well as light-independent interaction in the case of the Y272H phytochrome mutant, supporting the hypothesis that the Y272H mutant mimics the Pfr signalling conformation constitutively. Moreover, we found the N-terminal extension is particularly important for this interaction as no interaction was detected between the PGP construct and PIF6. This conclusion is consistent with experiments which showed that PIF6 suppresses dark reversion of NPGP but not PGP. Also, the PHY domain seems to be dispensable for phytochrome interaction with PIFs, since the Y272H mutant of the NPG construct still bound PIF6. This is consistent with earlier in planta studies which had shown that an NPG construct could trigger normal photomorphogenesis when it is dimerised and localised in the nucleus. Our studies emphasis the indispensable role of NTE in phyB(NPGP)-PIF interaction which should be taken into consideration in crystallisation trials of the complexes.
Keywords: ddc:570